The Role of Digital Transformation in Human Resource Development: Challenges and Opportunities for Modern Organizations - Jufrina Mandulangi; Juliet Pauladel Truly Makinggung (An-naba : Jurnal Pendidikan dan Pengabdian Masyarakat, 2026)
The rapid advancement of digital technologies has fundamentally reshaped the landscape of human resource development (HRD). This article explores the intersection between digital transformation and HRD, focusing on how organizations can leverage technology to enhance employee competencies, foster continuous learning, and improve overall performance. Drawing on a systematic literature review, the study identifies key challenges—including resistance to change, skill gaps, and data privacy concerns—alongside opportunities such as personalized learning, real-time performance analytics, and increased organizational agility. The findings suggest that successful digital HRD requires strategic alignment between technology adoption, leadership commitment, and a culture of lifelong learning. Practical implications for HR managers and policymakers are discussed.